A novel approach for the fabrication of 3D-printed dental membrane scaffolds including antimicrobial pomegranate extract. - AKSU, MEHMET BURAK (My University, 2023)
In this study, a dental membrane scaffold was fabricated using a 3D printing technique, and the antimicrobial effect of pomegranate seed and peel extract were investigated. For the production of the dental membrane scaffold, a combination of polyvinyl alcohol, starch, and pomegranate seed and peel extracts was used. The aim of the scaffold was to cover the damaged area and aid in the healing process. This can be achieved due to the high antimicrobial and antioxidant content of pomegranate seed and peel extracts (PPE: PSE). Moreover, the addition of starch and PPE: PSE improved the biocompatibility of the scaffold, and their biocompatibility was tested using human gingival fibroblast (HGF) cells. The addition of PPE: PSE into the scaffolds resulted in a significant antimicrobial effect on S. aureus and E. faecalis bacteria. Moreover, different concentrations of starch (1%, 2%, 3% w/v) and pomegranate peel and seed extract (3%, 5%, 7%, 9%, and 11% PE v/v) were analyzed to obtain the ideal dental membrane structure. The optimum starch concentration was chosen as 2% w/v due to it giving the scaffold the highest mechanical tensile strength (23.8607 ± 4.0796 MPa). The pore sizes of each scaffold were studied by SEM analysis, and pore sizes were arranged between 155.86 and 280.96 µm without any plugging problems. Pomegranate seed and peel extracts were obtained by applying the standard extraction method. High-performance liquid chromatography was performed using the diode-array detection (HPLC-DAD) technique to analyze the phenolic content of the pomegranate seed and peel extracts. Two phenolic components of the pomegranate seed and peel extracts were investigated in the following amounts: fumaric acid (17.56 µg analyte/mg extract) and quinic acid (18.79 µg analyte/mg extract) in pomegranate seed extract and fumaric acid (26.95 µg analyte/mg extract) and quinic acid (33.79 µg analyte/mg extract) in pomegranate peel extract.
Keywords: dental membrane; polyvinylalcohol; pomegranate; starch; scaffolds; 3D printing